Disaster Risk Reduction in Muslim Residential Areas Based on Community Participation (The Case of Kayupuring Petungkriyono Pekalongan) - Mohammad Irsyad; Abdul Hamid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2020)
The purpose of this study is to practice the commands in Islam to participate in disaster management through appropriate mentoring activities to support community members in the community in terms of disaster risk reduction in Kayupuring Village. This study uses the Participatory Action Research method. The research was conducted in Kayupuring Village with the research subjects of community members, especially those who are members of the Tourism Awareness Group (POKDARWIS) and Karang Taruna who have an interest in realizing an independent village in facing potential disaster threats and increasing the role of the community in processing resources to reduce disaster risk. This research resulted in several activities, including 1) Socialization and Formation of a Disaster Resilient Village Volunteer Team (Destana); 2) Revitalization and Disaster Risk Assessment; 3) Self-Assessment and Creation of Evacuation Paths; and 4) Tree Planting.